Traditional and Local Ecological Knowledge for Land Use Mapping - Norizawati, Mohd Ayob; Tarmiji, Masron; Norhasimah, Ismail (Trans Tech Publications, 2015)
and use changes are a key driver in global environmental changes and had a significant impact on the climate at all scales. Various human activities that took place thousands of years ago have an impact on the earth's surface. Today, with the limited supply and high demand, land use crisis became a big issue for the most countries. Changes in land use are not actually only providing a history of the area, but it also describes the way of life of its local communities. In the interdisciplinary research for land use study, cultural values, knowledge and perceptions of knowledge has been recognized as a major factor in determining the adopted approach applied in land use management in that area. Therefore, this paper tries to evaluate the role and potential of the integration of TLEK and GIS in mapping the series of changes in land use.Keyword: Local knowledge, TLEK, land use mapping & conceptual framework